Safety and Effectiveness of Triple-Antenna Hepatic Microwave Ablation - Nikola Bošković; Srdjan Nikolić; Branislav Radjenović; Marija Radmilović-Radjenović (Bioengineering)
Microwave ablation is becoming a standard procedure for treating tumors based on heat generation, causing an elevation in the tissue temperature level from 50 to 60 °C, causing tissue death. Microwave ablation is associated with uniform cell killing within ablation zones, multiple-antenna capability, low complication rates, and long-term survival. Several reports have demonstrated that multiple-antenna microwave ablation is a promising strategy for safely, rapidly, and effectively treating large tumors. The key advantage of multi-antenna tumor microwave ablation is the creation of a large, well-defined ablation zone without excessively long treatment times or high power that can damage healthy tissue. The strategic positioning of multiple probes provides a fully ablated volume, even in regions where individual probe damage is incomplete. Accurate modeling of the complex thermal and electromagnetic behaviors of tissue is critical for optimizing microwave ablation because material parameters and tissue responses can change significantly during the procedure. In the case of multi-antenna microwave ablation, the calculation complexity increases significantly, requiring significant computational resources and time. This study aimed to evaluate the efficacy and safety of liver percutaneous microwave ablation using the simultaneous activation of three antennas for the treatment of lesions larger than 3 cm. Based on the known results from a single-probe setup, researchers can estimate and evaluate various spatial configurations of the three-probe array to identify the optimal arrangement. Due to the synergistic effects of the combined radiation from the three antennas, the resulting ablation zone can be significantly larger, leading to better outcomes in terms of treatment time and effectiveness. The obtained results revealed that volumetric damage and the amount of damaged healthy tissue are smaller for a three-antenna configuration than for microwave ablation using a single-antenna and two-antenna configurations.